2008
DOI: 10.2353/ajpath.2008.070937
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Smad3 Induces Neutrophil Migration after Cutaneous Irradiation

Abstract: Our previous work showed that 6 weeks after cutaneous irradiation, mice null (knockout, KO) for Smad3, a cytoplasmic downstream mediator of transforming growth factor-beta, demonstrate less epidermal acanthosis and dermal inflammation than wild-type (WT) Smad3 mice. Analysis of the kinetics of inflammation showed that 6 to 8 hours after skin irradiation, there was a transient sevenfold increase in neutrophil influx in Smad3 KO mice compared with WT. Herein we describe bone marrow transplantation and skin graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Interestingly, cell counts decreased after 8 wk CS in Smad3 Ϫ/Ϫ mice, while they at the same time significantly increased in CS-exposed Smad3 ϩ/ϩ . This observation points perhaps toward a dysregulated immune response following continuous CS challenge, which is in line with previous studies showing that TGF-␤ signaling via Smad3 is required for an appropriate regulation of the immune response, in particular for normal T-lymphocyte and neutrophil activity (13,28,55). It is also plausible that release of elastolytic enzymes from neutrophils contribute to the progression of emphysema and perpetuate inflammatory cell recruitment to the lung.…”
Section: L397supporting
confidence: 87%
“…Interestingly, cell counts decreased after 8 wk CS in Smad3 Ϫ/Ϫ mice, while they at the same time significantly increased in CS-exposed Smad3 ϩ/ϩ . This observation points perhaps toward a dysregulated immune response following continuous CS challenge, which is in line with previous studies showing that TGF-␤ signaling via Smad3 is required for an appropriate regulation of the immune response, in particular for normal T-lymphocyte and neutrophil activity (13,28,55). It is also plausible that release of elastolytic enzymes from neutrophils contribute to the progression of emphysema and perpetuate inflammatory cell recruitment to the lung.…”
Section: L397supporting
confidence: 87%
“…Interestingly, exogenous administration of either GM-CSF or G-CSF to animals can provide some protection against lethal radiation doses [127–129] and has been delivered to patients following radiation accidents [130]. In addition to hematopoietic recovery, the effect of these growth factors may relate to neutrophil migration to irradiated sites and subsequently improved repair of radiation damage [131]. These data fit with the repair role of myeloid cells in the tumor discussed earlier, and in this context of cancer-driven myeloid expansion, GM-CSF and G-CSF may improve recovery of the tumor from radiation damage, permitting outgrowth of residual cancer cells.…”
Section: Mdsc Granulocytes and Macrophagesmentioning
confidence: 99%
“…Transgenic mouse models with reduced proinflammatory radiation response are not necessarily associated with tissue radioprotection. For example, SMAD3 Ϫ/Ϫ mice are protected against radiation-induced skin injury despite a transient strong increase in neutrophil influx (24,25). In the same way, we recently showed that radiation proctitis is attenuated in mast cell-deficient mice compared with WT mice and that it is associated with increased tissue neutrophil influx and expression of several inflammatory mediators immediately after radiation exposure (26).…”
Section: Discussionmentioning
confidence: 85%